PHYSICAL EDUCATION AS A CURRICULAR COMPONENT: INTELLECTUALS, KNOWLEDGE AND TEACHING - Furtado, Renan Santos (2023)
This is a theoretical study that aimed to reflect on the theoretical-practical developments of what it means to treat Physical Education as a curricular component. The motivation for writing this work goes back to the author's experiences as a basic education teacher. For the theoreticalmethodological progress of the study, we made use of a specialized discussion of the area on the subject, guided by questions related to the Physical Education teacher as an intellectual, the meaning of the term curricular component, the knowledge that Physical Education addresses at school and the didactic consequences of thinking about the thematization of body culture of movement in basic schooling. The study pointed out that the condition of a curricular component delegates to Physical Education a set of responsibilities and rights, which revolve around the tension between its historical logic of school activity, with the contemporary meaning that we claim as a curricular component with the status of a discipline school education.